Environmental degradation in emerging-market economies of Africa: evaluating impacts of human capital development, international trade, renewable energy consumption, and urbanization - Bajja, Salwa; El-Bouayady, Rachida; Çelik, Ali; Ahmed, Zahoor; Radoine, Hassan (Frontiers in Environmental Science, 2024)
This research explores the impact of human capital development, international trade, financial development, renewable energy consumption, and urbanization on environmental degradation in emerging-market economies in Africa. The study adopts a quantitative approach using panel data from 8 African countries between 1991 and 2021. The study adopted the method of Mean Group Dynamic Least Squares and Method of moments quantile regression methods to estimate the empirical relationship between the variables of interest. The findings indicate that urbanization, energy consumption, economic growth, and human capital development have significant and positive effects on environmental degradation, while financial development, renewable energy consumption, manufacturing activities, and international trade have a significant negative effect on environmental degradation. The study concludes that policymakers in emerging-market economies in Africa need to promote financial development and renewable energy consumption while simultaneously addressing the negative impacts of urbanization on the environment to achieve sustainable economic growth.